DEVELOPMENT OF PHYSICAL QUALITIES OF YOUNG GYMNASTS - Ziyodullayeva Madina Ziyodullayevna (European Science Publishing, 2024)
The article provides examples of the development of physical qualities of young gymnasts.
Keywords: gymnastics, development, flexibility, energy, sharpness, muscles, squatting.